Speaking Proficiency Among English Specific Purpose Students: A Literature Review On Assessment And Pedagogical Approaches - Shella Gherina Saptiany; Bayu Ade Prabowo (LITERACY : International Scientific Journals of Social, Education, Humanities, 2024)
Developing speaking proficiency is a critical goal for students in English for Specific Purposes (ESP) programs, as effective oral communication skills are essential for their future professional success. This literature review aims to synthesize existing research on assessing and enhancing speaking proficiency among ESP students through various pedagogical approaches. The review explores three main themes: 1) the multifaceted nature of speaking proficiency for ESP students, encompassing linguistic competencies, pragmatic awareness, and intercultural communicative competence; 2) assessment methods for evaluating ESP students' speaking abilities, including standardized tests, performance-based assessments, and contextualized rubrics; and 3) pedagogical approaches for improving speaking skills, such as task-based language teaching, project-based learning, technology integration, and explicit instruction on pragmatics and discourse strategies. The literature review highlights the importance of aligning assessment practices and instructional methods with the specific communicative needs and target language use situations of ESP learners in their respective professional domains. By critically analyzing and synthesizing the findings from relevant studies, this review contributes to a deeper understanding of best practices for assessing and developing speaking proficiency in ESP contexts. Implications for curriculum design, teacher training, and future research directions are discussed, with the ultimate goal of better preparing ESP students to become effective and confident communicators in their chosen fields.